2019
DOI: 10.1093/ntr/ntz043
|View full text |Cite|
|
Sign up to set email alerts
|

How Does Smoking and Nicotine Dependence Change After Onset of Vaping? A Retrospective Analysis of Dual Users

Abstract: Introduction Although some smokers switch to exclusive use of electronic cigarettes (e-cigarettes), others become dual users of combustible cigarettes and e-cigarettes. Little is known about how the onset of vaping affects the use of and dependence on combustible cigarettes or total nicotine use and dependence, which may influence health-related and cessation outcomes. Using self-report data of current combustible and e-cigarette use and retrospective recall of pre-vaping smoking in a sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 54 publications
8
42
0
1
Order By: Relevance
“…Mirroring the prevalence in Canada and consistent with extant studies [1,4,38], 19% of young adults in this study had used e-cigarettes in the past year, including relatively more males than females. Also concordant with previous reports [1,4,24,25], most e-cigarette users smoked conventional cigarettes and two-thirds reported ND symptoms, with the proportion increasing to 80% among those who vaped nicotine-containing eliquid exclusively. Only one-quarter of cigarette users had used e-cigarettes to quit in the past year.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Mirroring the prevalence in Canada and consistent with extant studies [1,4,38], 19% of young adults in this study had used e-cigarettes in the past year, including relatively more males than females. Also concordant with previous reports [1,4,24,25], most e-cigarette users smoked conventional cigarettes and two-thirds reported ND symptoms, with the proportion increasing to 80% among those who vaped nicotine-containing eliquid exclusively. Only one-quarter of cigarette users had used e-cigarettes to quit in the past year.…”
Section: Discussionsupporting
confidence: 92%
“…A US report using nationally representative data found that only 13% of young adult lifetime e-cigarette users reported using e-cigarettes as a cessation aid and these individuals were less likely to report cessation in the pastyear [56]. It is possible that, because of nicotine in ecigarettes (even in e-cigarettes labelled nicotine-free [53]), young adults who try to quit using nicotinecontaining e-cigarettes in fact contribute to or increase their ND level [25] leaving them craving nicotine. Polytobacco users in general, are more likely to report ND symptoms than cigarette-only smokers [25,57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 Martinez ve ark.nın yaptığı retrospektif bir analizde, geleneksel sigara kullanımı ve E-sigaranın birlikte kullanımının (ikili kullanım) zamanla geleneksel sigara kullanımını azalttığı, ancak toplam nikotin kullanımı ve bağımlılığı artırdığı bulunmuştur. 66 Kulik ve ark.nın 2018 yılında, 28 Avrupa Birliği ülkesi ile Büyük Britanya'da yaptıkları kesitsel bir araştırmada, ikili kullanıcıların sadece geleneksel sigara kullanıcılarına göre, günlük olarak önemli ölçüde daha fazla sigara kullandığı rapor edilmiştir. 67 Literatürde bildirilen çalışma so-nuçları dikkate alındığında; E-sigaraların içerdiği nikotin nedeni ile bağımlılığı sürdüreceği ve dolayısı ile geleneksel sigara kullananlarda sigarayı bırakmayı zorlaştıracağı, hiç kullanmayanlarda ise kademeli olarak geleneksel sigara kullanımına yol açacağı bildirilmektedir.…”
Section: E-si̇garalarin Geleneksel Si̇garayi Biraktirmaya Etki̇si̇unclassified